2021
DOI: 10.1186/s12885-021-08105-y
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the characteristics and predicting the survival of patients with head and neck melanoma versus body melanoma: a population-based study

Abstract: Background Previous studies reported cutaneous melanoma in head and neck (HNM) differed from those in other regions (body melanoma, BM). Individualized tools to predict the survival of patients with HNM or BM remain insufficient. We aimed at comparing the characteristics of HNM and BM, developing and validating nomograms for predicting the survival of patients with HNM or BM. Methods The information of patients with HNM or BM from 2004 to 2015 was … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
1
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 44 publications
1
14
1
6
Order By: Relevance
“…A study on 70 605 primary invasive melanomas from the Surveillance, Epidemiology and End Results (SEER) database found that head and neck melanoma made up 21.3% of cases compared with body melanoma and contained older patients (mean age 64.6 vs. 57) 16 . This contrasts with the current study, in which the head and neck melanoma cohort made up only 14.0% of primary invasive melanomas.…”
Section: Discussioncontrasting
confidence: 98%
See 1 more Smart Citation
“…A study on 70 605 primary invasive melanomas from the Surveillance, Epidemiology and End Results (SEER) database found that head and neck melanoma made up 21.3% of cases compared with body melanoma and contained older patients (mean age 64.6 vs. 57) 16 . This contrasts with the current study, in which the head and neck melanoma cohort made up only 14.0% of primary invasive melanomas.…”
Section: Discussioncontrasting
confidence: 98%
“…Nodular melanoma cause a disproportionate number of deaths 11 and thin melanomas can also lead to death 16 . Consistent with this, in the current study, five NM and two SSM, one with a Breslow thickness of 0.5 mm and a diameter of 10 mm, were directly linked to patient death.…”
Section: Discussionsupporting
confidence: 87%
“…However, head and neck melanoma showed the greatest improvement in survival rate and the best ICIs efficacy between the two eras. This contradictory result may be explained by the following reasons: According to epidemiological surveys, head and neck melanoma has a worse prognosis than CM from other body areas ( 29 , 30 ). Head and neck have rich vascularization and lymphatic drainage, melanoma is prone to metastases and even more likely to develop brain metastases ( 31 , 32 ).…”
Section: Discussionmentioning
confidence: 99%
“…(c) The following methods were used to construct and verify the prediction model, including multiple fractional multivariate models (MFP model), full model, stepwise selected model (stepwise model), bootstrap full (bootstrap resampling 500 times), and bootstrap stepwise (bootstrap resampling 500 Times). (d) The corresponding nomogram was constructed based on the best model described above, and then we used the “DynNom” package to construct a corresponding online dynamic nomogram ( 15 ). (e) The missing value of variables included in our study was very few, so there was no special handling of the missing values during model building.…”
Section: Methodsmentioning
confidence: 99%